THE EFFECT OF DRAWING TECHNIQUE ON THE BIOLOGY SUCCESS OF PROSPECTIVE SCIENCE TEACHERS - Sibel DEMİR (Fırat University, 2019)
Since it includes many sub concepts; the subject of animal tissues, which is theoretically both abstract and concrete, is one of the subjects that the students have difficulty in biology. In order to be able to find a solution to this problem; it has been thought that for prospective teachers, in understanding and integrating the subject of animal tissues, integrating their abstract and theoretical knowledge with the drawings they make will help to constitute a more effective knowledge schema. The aim of this study is to determine the effect of drawing technique in understanding the animal tissues and differentiating between tissue elements which are the contents of General Biology-I and General Biology Laboratory-I lessons. The method of pre-test and post-test design with control group was employed. As a result of the analyses, significant results of p